2014
DOI: 10.11648/j.ijll.20140203.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Summarizing Strategy on Reading Comprehension of Iranian Intermediate EFL Learners

Abstract: Reading comprehension plays a significant role in educational success. In spite of its importance, students still have difficulties in understanding texts. One solution to the problem of poor reading comprehension is the learning of reading strategies. The current study examined the effect of summarizing strategy on reading comprehension of Iranian intermediate EFL learners. Sixty-one students were selected and randomly divided into two control and experimental groups. The homogeneity of their proficiency leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Paksadian and Rasekh (2012) reported in their study that summarization strategy created a positive effect in the respondents' level of comprehending reading comprehension texts. Similarly, in another study conducted by Khoshsima and Tiyar (2014), the findings also indicated that summarizing strategy enhances the reading comprehension skills of the students. All these clearly show that if low proficiency students employ this strategy, they will be able to improve their level of comprehension.…”
Section: Suggested Cognitive Reading Strategies For Low Proficiencmentioning
confidence: 51%
“…Paksadian and Rasekh (2012) reported in their study that summarization strategy created a positive effect in the respondents' level of comprehending reading comprehension texts. Similarly, in another study conducted by Khoshsima and Tiyar (2014), the findings also indicated that summarizing strategy enhances the reading comprehension skills of the students. All these clearly show that if low proficiency students employ this strategy, they will be able to improve their level of comprehension.…”
Section: Suggested Cognitive Reading Strategies For Low Proficiencmentioning
confidence: 51%
“…According to the findings, sufficient time is needed to develop particular reading skills and strategies such as summarizing strategy and indeed encourage content reading intending to make students ready for autonomous reading and understanding (Khoshsima & Rezaeian Tiyar, 2014). Through the summarizing strategy instruction, teachers can identify students' weaknesses in reading comprehension and make the essential efforts to solve their comprehension problems as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Often, they face problems even with the typical question and answer format that is provided after they read a passage. Research (Dole, Brown, & Trathen, 1996;Janzen, 2003;Karbalaei & Rajyashree, 2010;Khoshsima & Rezaeian Tiyar, 2014;Pakzadian & Eslami Rasekh, 2012;Nurhayati, 2014;Roohani, et al, 2015;Deshpande, 2016;Teng. 2016;Damayanti, 2017) has shown that together with direct instructions when students are taught reading strategies this will improve not only their comprehension of the reading passage but also their performances on the tests.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the knowledge or task variables, strategy use has rarely been included as a factor in WM studies, especially in L2 contexts. Although it has long been recognized as an important facilitator of various aspects of L2 acquisition, including L2 RC (e.g., Khoshsima & Tiyar, 2014;Malcom, 2009;Shang, 2010), studies that examined strategy use in relation to WM's function in L2 reading are not easily found. Based on a study involving L1 adult learners, Naumann, Richter, Christmann, and Groeben (2008) claimed that WM capacity was a prerequisite for strategy training to be effective in learning.…”
Section: Review Of Literaturementioning
confidence: 99%